Myśliwy w parku narodowym? Rekonstrukcja dyskursów wokół konfliktu ekologicznego na terenie Słowińskiego Parku Narodowego - Mielewczyk, Marcin (Studia Etnologiczne i Antropologiczne, 2017)
The lack of respect for nature resulting from anthropocentric axiology and manifesting itself in the exploitation of natural resources is considered the root cause of the ecological crisis. In this context, on the basis of the author’s ethnographic studies conducted in the area of Słowiński National Park, the author addresses the question of defining what that protection is and how it should be carried out. The author presents the analysis of shaping the local space of identification of the residents of Smołdzino municipality. The strict protection plan has turned out to be destructive in terms of the local infrastructure, social relations, tourism, and it has also proved to be totally inadequate for the protection of virgin land.